2017
DOI: 10.4103/2303-9027.208177
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of endoscopic ultrasound-fine needle aspiration of solid lesions over time: Experience from a new endoscopic ultrasound program at a Canadian community hospital

Abstract: Background and Objectives:A Canadian Community Hospital launched a new Endoscopic Ultrasound (EUS) Program in 2011. The aim of this study was to report the accuracy of EUS-fine needle aspiration (EUS-FNA) of solid lesions over time as it pertains to cytotechnologists’ involvement and learning curves.Methods:The electronic medical records of patients that had a EUS from July 2011 to January 2014 were retrospectively reviewed. Only solid lesions with FNA sampling were included in the study. The primary outcome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…A retrospective study on 583 patients reported a strong correlation between diagnostic yield and the size of the lesion[ 5 ]. Another retrospective study involving 271 patients reported that the size of the lesion was an independent factor for tissue acquisition[ 8 ]. These indicate that care is needed with smaller lesions and the type of needle used, a modifiable factor, become even more important in smaller lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study on 583 patients reported a strong correlation between diagnostic yield and the size of the lesion[ 5 ]. Another retrospective study involving 271 patients reported that the size of the lesion was an independent factor for tissue acquisition[ 8 ]. These indicate that care is needed with smaller lesions and the type of needle used, a modifiable factor, become even more important in smaller lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is minimally-invasive and well-tolerated by patients[ 1 , 2 ]. A number of factors have been shown to influence successful tissue acquisition including lesion position[ 3 , 4 ], lesion size[ 5 - 8 ], needle type[ 9 - 12 ], needle size[ 13 - 16 ], number of passes[ 17 - 21 ], technical skills[ 22 - 25 ] and the presence of rapid on-site cytological evaluation (ROSE)[ 1 , 26 - 28 ].…”
Section: Introductionmentioning
confidence: 99%